Notary's Responsibility in Preventing and Overcoming Money Laundering Crimes in Pekalongan Regency - Putri, Genna Ellana (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The purpose of this study is to analyze: 1) To find out and analyze the responsibility of Notaries in Preventing and Overcoming Money Laundering Crimes in Pekalongan Regency. 2) To find out and analyze the Obstacles and Solutions in preventing and overcoming money laundering crimes in the Notary profession in Pekalongan Regency. The method of approach in writing this research is the Juridical Sociological approach. The data used in this study are primary data including the 1945 Constitution; Law No. 2 of 2014; Law on the Prevention and Eradication of Money Laundering; Notary Code of Ethics; Civil Code and Criminal Code. As well as secondary data containing books and other supporting documents. Data collection of research using interview techniques and document studies or library materials. The data analysis method used in analyzing the data is an interactive qualitative model analysis as proposed by Miles and Huberman. The results of the study indicate that Notaries are required to be active in making efforts to prevent money laundering, especially from parties who are their clients and because Notaries as a legal profession should also be able to integrate with other professions / other law enforcers to become professional law enforcers in law enforcement duties. The role of the legal profession can only be carried out properly if it receives support for strengthening the code of ethics of the legal profession which until now is still somewhat vague or unclear, so that malpractice does not occur in the legal process. Notaries in Pekalongan Regency must apply the principle of recognizing service users (Know Your Consumer). The obstacles faced by notaries in efforts to eradicate money laundering are related to the theory of absolute secrecy, especially related to the obligation to maintain client confidentiality. In Indonesia, notaries have a legal obligation to maintain the confidentiality of all matters relating to the deeds they make.